Pengaruh Green Accounting, Kinerja Lingkungan, dan Leverage, terhadap Kinerja Keuangan yang Dimoderasi oleh Corporate Social Responsibility - Refalina, Aulia; Hamidi, Masyhuri; Rahim, Rida (SAFE-Network, 2024)
The purpose of this study is to determine the influence of Green Accounting, and Leverage moderated by Corporate Social Responsibility on the Company's Financial Performance. The research method used is a quantitative method. The data used in this study is secondary data in the form of financial statements from the website (www.idx.co.id). The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The sample was selected from the purposive sampling method and obtained a sample of 38 companies from several criteria that had been set. The analysis technique used in this study is panel regression analysis with the help of STATA version 14.2. The results of the analysis show that Green Accounting does not have a significant positive effect on financial performance. Leverage has a significant negative effect on financial performance. Green accounting moderated by Corporate Social Responsibility on the Company's Financial Performance has a negative effect. Leverage moderated by Corporate Social Responsibility has a significant positive effect on the Company's financial performance. This research can contribute to adding literature related to additional considerations such as Green Accounting, leverage and CSR for investors in evaluating the Company's potential.